Regulation of protein function by native metastability - Lee, C; Park, SH; Lee, MY; Yu, MH (NATL ACAD SCIENCES, 2000)
In common globular proteins, the native form is in its most stable state. In contrast, each native form exists in a metastable state in inhibitory serpins (serine protease inhibitors) and some viral membrane fusion proteins, Metastability in these proteins is critical to their biological functions. Mutational analyses and structural examination have previously revealed unusual interactions, such as side-chain overpacking, buried polar groups, and cavities as the structural basis of the native metastability. However, the mechanism by which these structural defects regulate protein functions has not been elucidated. We report here characterization of cavity-filling mutations of alpha(1)-antitrypsin, a prototype serpin. Conformational stability of the molecule increased linearly with the van der Waals volume of the side chains. Increasing conformational stability is correlated with decreasing inhibitory activity. Moreover, the activity loss appears to correlate with the decrease in the rate of the conformational switch during complex formation with a target protease. These results strongly suggest that the native metastability of proteins is indeed a structural design that regulates protein functions.
Keywords: PLASMINOGEN-ACTIVATOR INHIBITOR-1; CAVITY-CREATING MUTATIONS; INFLUENZA HEMAGGLUTININ; HYDROPHOBIC CORE; HUMAN ALPHA(1)-ANTITRYPSIN; CONFORMATIONAL CHANGE; CRYSTAL-STRUCTURE; LOOP INSERTION; MECHANISM; SERPINS